Kualitas Layanan, Produk, Lokasi, dan Harga terhadap Keputusan Konsumen - Muhammad Dodik; Abadi Sanosra; Ahmad Izzuddin (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of service quality, product, location and price on purchasing decisions at the Basmalah Tanggul Store. This research is a causal relationship research, which aims to measure the strength of the relationship between two or more variables, and also shows the direction of the relationship between the independent variable and the dependent variable. The sample used is 100 respondents. Methods of data collection were carried out through observation, interviews and questionnaire surveys. The sampling method used is the purposive sampling method, and the analysis media uses multiple linear regression. The results show, a) Service has an Arithmetic significance value of 0.000 and less than 0.05, and arithmetic (5.601) > t table (1.6609); b) the product has a statistical significance value of 0.000 and less than 0.05 and the total t count (4.746) > t table (1.6609); c) the position has a statistical significance value of 0.001 and less than 0.05 and count (3.346) > t table (1.6609); d) the price has a statistical significance value of 0.000 and less than 0.05 and count (4.367) > t table (1.6609). In conclusion, service quality, product, location, and price have a significant effect on purchasing decisions at the Basmalah Tanggul store. Keywords: Quality of Service, Product, Location, Price, and Purchase Decision